the hardy boys mystery stories 57 : the firebird rocket - Dixon, Franklin W.; Franklin W. Dixon (New York Grosset & Dunlap, 1978)
The Firebird Rocket (#57 in the Hardy Boys series) follows Frank and Joe Hardy as they travel to Australia to locate a kidnapped rocket scientist,Dr. Balthazar, whose disappearance threatens the launch of a new, top-secret Firebird Rocket. The brothers face mortal danger, including being captured by villains, before rescuing the scientist and stopping the saboteurs.
English